The effect of the Fourier number on calculation of an unsteady heat transfer of building walls - Pupeikis, Darius; Stankevičius, Vytautas; Burlingis, Arūnas (Journal of Civil Engineering and Management, 2010)
When the temperature changes in any side of construction, the heat flow diffusing through construction also changes and it is varying until the stabilized steady state conditions is reached. In real terms, the heat exchange process in buildings is an unsteady state, consequently varying in time. Volatility of the heat exchange process is influenced by oscillating external temperature, internal heat gains, solar radiation and other factors that affect the heat balance of building. While calculating unsteady heat exchanges, it is important to divide the material into the right number of conditional layers. A conditional layer is material's thickness, in which an assumed process of steady heat transfer takes place. The time step is the second parameter which affects the accuracy of calculation of unsteady heat transfer. This parameter defines time during which temperature diffuses step by step through the conditional layer. Thermal diffusivity is the last parameter, which defines the equalization speed of the temperature in conditional layer. A combination of all these parameters is expressed as the Fourier number. Our research has showed that it's rational to divide layers of enclosure into equal thermal diffusions. Also, the cooling (heating) speed and the acceleration values of conditional layers significantly affect the accuracy of calculation.First Published Online: 24 Jun 2011